Health Education Intervention with Social Media Reminder and Audiovisual Approach to Improve Medication Compliance and Tuberculosis Prevention Behavior - Hotmaida Siagian; Dony Sulystiono; Muhammad Afif Hilmi Masyfahani (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2022)
Tuberculosis is a disease that is difficult to treat even though it has been controlled with the Directly Observed Treatment, Short-course chemotherapy (DOTS) strategy since 1995. This study aims to analyze the effect of health education interventions with social media reminder and audiovisual approaches on medication adherence and behavior. prevention of tuberculosis transmission at the Wonoayu Health Center, Sidoarjo, Indonesia. The design of this study was a non-equivalent control group pretest-posttest. The research subjects were 70 tuberculosis patients who were selected by purposive sampling technique. After collecting data on compliance and prevention, data analysis was carried out using the t-test. The p value of the difference in adherence test was 0.000, while the difference in prevention behavior was 0.000. Furthermore, it was concluded that the health education intervention with a social media reminder and audiovisual approach was effective in increasing medication adherence and preventing tuberculosis transmission. Keywords: tuberculosis; health education; medication adherence; Tuberculosis prevention behavior